Environmental drivers of rhodolith beds and epiphytes community along the South Western Atlantic coast. (February 2020) - Carvalho, Vanessa F.; Assis, Jorge; Serrão, Ester A.; Nunes, José M.; Anderson, Antônio B.; Batista, Manuela B.; Barufi, José B.; Silva, João; Pereira, Sonia M.B.; Horta, Paulo A.
Abstract: Environmental conditions shape the occurrence and abundance of habitat-building organisms at global scales. Rhodolith beds structure important hard substrate habitats for a large number of marine benthic organisms. These organisms can benefit local biodiversity levels, but also compete with rhodoliths for essential resources. Therefore, understanding the factors shaping the distribution of rhodoliths and their associated communities along entire distributional ranges is of much relevance for conservational biology, particularly in the scope of future environmental changes. Here we predict suitable habitat areas and identify the main environmental drivers of rhodoliths' variability and of associated epiphytes along a large-scale latitudinal gradient. Occurrence and abundance data were collected throughout the South-western Atlantic coast (SWA) and modelled against high resolution environmental predictors extracted from Bio-Oracle. The main drivers for rhodolith occurrence were light availability and temperature at the bottom of the ocean, while abundance was explained by nitrate, temperature and current velocity. Tropical regions showed the highest abundance of rhodoliths. No latitudinal pattern was detected in the variability of epiphytes abundance. However, significant differences were found between sampled sites regarding the composition of predominant taxa. The predictors influencing such differences were temperature and nitrate. The Tropical region is abundant in species with warm-water affinities, decreasing toward warm temperate region. The expressive occurrence of tropical species not referred before for warm temperate beds indicate a plausible tropicalization event. Highlights: The main drivers for rhodolith occurrence were light availability and temperature at the bottom. The abundance of the rhodoliths was explained by nitrate, temperature and current velocity. Tropical regions showed the highest abundance of rhodoliths. The epiphytes composition was significantly different between the three regions. Temperature and nitrate were the major drivers of the epiphyte flora.